Ghana Agriculture Sector Policy Note : Transforming Agriculture for Economic Growth, Job Creation, and Food Security (World Bank, Washington, DC, 2017)
The objective of this note is to help the Ministry of Food and Agriculture (MoFA) identify strategic policy directions and reform areas that are fundamental to accelerate and sustain agriculture sector growth. Sustained agricultural growth will contribute to overall resiliency ofthe economy as it undergoes structural transformation as it moves beyond lower middle-income status.The Agriculture Sector Policy Note is based on a number of sector studies and reports prepared by the Bank to support the existing investment projects. The objective of the Agricultural Sector Policy Note is to help Ghana achieve transformation and modernization of its agriculture sector. There are both challenges and opportunities towards achieving transformation and modernization of the agriculture sector in Ghana. The agricultural sector accounts for one fifth of Ghana’s Gross Domestic Product (GDP), employs nearly half of the workforce and is the main source of livelihood for the majority of the country’s poorest households.Ghana’s agricultural sector is characterized by low yields for both staple and cash crops.Ghana is a net importer of basic foods (raw and processed) including rice, poultry, sugar, and vegetable oils.Ghana has significant agricultural potential, particularly in the semi-arid NorthernSavannah (agro-)Ecological Zone (NSEZ), including the Afram Plains.The first priority is to improve public expenditure allocation and management as well as budget coordination in agriculture.The second priority is for MoFA to improve the collection and analysis of agriculturalstatistics to produce high quality and credible data for sector planning on a regular basis.Third, MoFA should improve the efficiency and effectiveness of input subsidy programs and fix gaps in input supply legislation.Fourth, prioritization of public investments in infrastructure, particularly in high agricultural potential areas, such as the NSEZ (including the Afram Plains) is critical to sustain Ghana’s agricultural growth. The government should promote coordination in the the implementation of its National Climate-Smart Agriculture and Food Security Action Plan, following the principles laid down in the National Climate Change Policy as well as the Intended Nationally Determined Contributions (INDC). The Government should also strengthen research on climate-smart agricultural technologies, strengthen the research-extension linkages to promote farmers’ technology adoption especially in fragile but high potential environments such as the NSEZ.